"Issues emanating from business impact on climate, environmental sustainability and CSR (corporate social responsibility): Steps towards pragmatism in extant realities": "Brand translation to equity from 'CSR as a potential tool in climate change mitigation and enhancing financial performances in organizations". Brand translation to equity - Olukorede Adewole (International Journal of Corporate Social Responsibility (JCSR), 2022)
The relationship between "CSR and Brands to the sustainable business environment coupled with climatic changes and environmental issues; "while emphasizing the potentials of 'CSR from brand reputation translation to equity as a tool for mitigating climate change mitigation and enhancing corporate financial performances has been extensively presented. A value - based dimension becomes clear realizing the link and connection between 'CSR, brand and brand association recognizing the key constructs and the translation of brand reputation to equity. The high R - value of 0.9753 between brand reputation and financial performances implies by adopting 'CSR which enhances brand reputation and translates to equity; corporations, companies and organizations can use 'CSR as a strategic tool for increased profitability and returns. It is extremely significant for companies, firms and corporations to take cognizance of 'CSR and recognize its key roles as brand promoter, gaining increased customer and brand loyalty, and translation of brand reputation to brand equity. Finally, relevant models and novel proposed models have been presented extensively; "giving insightful delineation of this crucial subject emphasizing and stressing the need to also look beyond the models rather giving a complimentary treatment and consideration. 'CSR as a strategic tool built and imbibed in business model becomes crucial and can be the key driver and tool to abate climate change, gain increased brand loyalty and enhance financial performances.
Keywords: 650; Brand reputation; Climate; CSR; Environmental Sustainability; Equity; Financial performance